2016
DOI: 10.1371/journal.pone.0154511
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Adiposity, Lipid Profile Disorders and the Metabolic Syndrome Occurrence in Premenopausal and Postmenopausal Women

Abstract: The aim of the study was the assessment of the dependencies between a woman’s menopausal status and adiposity, lipid profile and metabolic syndrome occurrence, as well as finding out whether the correlations between the socio-demographic profile and lifestyle elements and adiposity, lipid profile and the risk of MetS are the same before and after menopause. A cross-sectional study was carried out on 3636 women, aged between 40–59, which involved a questionnaire interview, anthropometric measurements and fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 66 publications
1
11
1
Order By: Relevance
“…However, the analytic approach controlled for the dyadic nature of the data, and an exploratory approach was appropriate given the paucity of research on dyadic weight management interventions with this population. Similar effect sizes have also been obtained in other studies examining associations between self-reported diet and exercise and weight outcomes in non-cancer samples [4345]. Additionally, although the sample was diverse with regard to race, age, and stage of non-metastatic disease, the sample represents a minority of those approached for participation.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, the analytic approach controlled for the dyadic nature of the data, and an exploratory approach was appropriate given the paucity of research on dyadic weight management interventions with this population. Similar effect sizes have also been obtained in other studies examining associations between self-reported diet and exercise and weight outcomes in non-cancer samples [4345]. Additionally, although the sample was diverse with regard to race, age, and stage of non-metastatic disease, the sample represents a minority of those approached for participation.…”
Section: Discussionsupporting
confidence: 74%
“…Exercise has shown inconsistent associations with weight loss in both cancer and non-cancer samples [4345]. However, the importance of exercise in weight management interventions for individuals with and without a cancer history should not be discounted.…”
Section: Discussionmentioning
confidence: 99%
“…Buonani et al 17 showed an average PFM score of 45.1% ± 5.5%, and in a part of the PONS Study, the average adiposity was 34.1% ± 6.7% for pre-menopausal women and 36.2% ± 6.5% for postmenopausal women. 21 The observed food profile had a reasonable quality, with a mean score of 34.5 ± 6.2 points. No updated references were found for the questionnaire "How is your diet?…”
mentioning
confidence: 84%
“…25 Relative to fruits and vegetables consumption, a part from the PONS Study showed that premenopausal and and postmenopausal period women, used to consume similar portions (4.06 ± 1.71 servings/day for premenopausal and 4.07 ± 1.71 portions / day for postmenopausal women). 21 Diet quality has implications on the health of menopausal women, and is related to several factors. In an American study, when evaluating the relationship between diet and optimism, healthy eating indexes had an inverse association with BMI, WC, history of diabetes or hypertension and depression.…”
mentioning
confidence: 99%
“…From the results of several studies, it was stated that regular physical activity had an influence on lipid profiles. 11,12 Whereas another study stated that there were no significant differences in lipid profile levels after and before physical activity was given. 13 During regular physical activity an increase in fatty acids in the blood is a raw material for the formation of energy in the muscles during physical activity, then these fatty acids will be transferred into the muscle as an energy source.…”
Section: Introductionmentioning
confidence: 99%